PERFORMANCE OF ENZYME LINKED IMMUNOSORBENT ASSAYVERSUS LATEX AGGLUTINATION TEST IN THE DIAGNOSIS OFACUTE GASTROENTERITIS BY ROTA VIRUS - Abood, Walaa Najm (Al-Nahrain Journal of Science, 2010)
In this study we use two types of methods for detecting Rota virus in 91 stool specimens from children with acute gastroenteritis. The aim of this study to determine the performance (sensitivity & specificity) of latex agglutination (LAT) and enzyme linked immunos-orbentassay (ELISA) for evaluation children acute gastroenteritis by Rotavirus.Fecal samples were collected from ninety one children suffering from acute gastroentritis. their age ranged between(1 132) months. The highest sensitivity was(92.5%) obtained with LAT followed by ELISA (84.09%). while the highest specificity was(93.6%) obtained with ELISA followed by LAT(86.3%). the highest predictive positivity value was obtained with ELISA(92.5%) followed by LAT (84.09%).LAT is easy to performance and gave high sensitivity with accepted specificity therefore, could be applied successfully for routine diagnosis and Epidemiological study. But ELISA techniques allow quantitative estimation of Rotavirus antigens.